Efficacy and safety of hydrokinesitherapy in patients with dystrophinopathy - Suslov, V. M.; Lieberman, L. N.; Carlier, P. G.; Ponomarenko, G. N.; Ivanov, D. O.; Rudenko, D. I.; Suslova, G. A.; Adulas, E. I. (Frontiers in Neurology, 2023)
Duchenne muscular dystrophy (DMD) is one of the most common forms of hereditary muscular dystrophies of childhood that is characterized by steady progression and early disability. It is known that physical therapy can slow down the rate of progression of the disease. According to world recommendations, pool exercises, along with stretching, are preferable for children with DMD, as they have a balanced effect on skeletal muscles and allow simultaneous breathing exercises. The aim of the study was to evaluate the effectiveness of regular pool exercises during 4 months of training according to the developed program in patients with Duchenne muscular dystrophy, capable of independent movement. According to the results of the study, a statistically significant improvement was identified in a 6-minute walking test 462,7 ± 6,2 m. on the baseline, 492,0 ± 6,4 m. after 4 months (p<0,001), timed functional tests: rising from the floor test 4,5 ± 0,3 sec. on the baseline, 3,8 ± 0,2 sec. after 4 months (p<0,001), a 10metre distance running test 4,9 ± 0,1 sec. on the baseline, 4,3 ± 0,1 sec. after 4 months (p<0,001), a 4-stair climbing test 3,7 ± 0,2 sec. on the baseline, 3,2 ± 0,2 sec. after 4 months (p<0,001), a 4-stair descent test 3,9 ± 0,1 sec. on the baseline, 3,2 ± 0,1 sec. after 4 months (p<0,001). Quantitative MRI of the skeletal muscles of the lower extremities with an assessment by water T2 using the method of three-exponential calculation did not demonstrate negative dynamics and an increase of edema in the muscles in comparison before and after training that can be regarded as a criterion for the safety of the exercises. Thus, a complex of dynamic aerobic exercises in water according to the developed program in patients with DMD can be regarded as effective and safe.